TikTok Social Media and Colloquial Discourse of Grade 4—6 Elementary School Children in Surabaya - Rafida Mumtaz; Irfa Rafiatuz Zukhrufin; Izzatin Nada Al Jannah; Pujo Sakti Nur Cahyo (Universitas Airlangga, 2022)
This study aims to explore how TikTok content consumptions affect daily language usage of 4th-6th graders in Surabaya elementary school. The popularity of TikTok as an entertainment platform has increased rapidly since Covid-19 pandemic. With thousands of content, some of TikTok users are children who are in the phase of imitation and building their language skills. By applying a qualitative approach based on interviews and observations, our findings suggest that during the pandemic, parental supervision of children's smartphone usage was very low. This creates a tendency for children to freely roam on various applications on their devices, including TikTok, which results in massive and uncontrolled patterns of content consumption. On further observations of content production activities and cross-platform online social interactions, findings revealed the tendency for these children to reproduce and imitate several vocabularies commonly found in TikTok content, such as anjing, goblok, kakak, butuh kontak, bang, lonte, and cok. In researchers’ observations, these vocabularies tend to have negative nuances because they contain swearing, disrespectful, and rude elements.